The First Wife - Spindler, Erica 1957- (Thorndike, Maine : Center Point Large Print, 2015)
"An idealistic young woman marries a man she barely knows only to discover his first wife disappeared under mysterious circumstances"--
Keywords: Married people -- Fiction; Missing persons -- Fiction; Large type books; Romantic suspense fiction